Chapter 1 INTRODUCTION The food commons are coming ... - Vivero-Pol, Jose Luis (Taylor & Francis, 2018)
This book aims to open that discussion in the belief that we can obtain for food at least some of the (though partial) successes that we have been able to obtain with water.